2022
DOI: 10.1101/2022.01.24.477630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DciA helicase operators exhibit diversity across bacterial phyla

Abstract: A fundamental requirement for life is replication of an organism's DNA. Studies in Escherichia coli and Bacillus subtilis have set the paradigm for how DNA replication occurs in bacteria. During replication initiation in E. coli and B. subtilis, the replicative helicase is loaded onto the DNA at the origin of replication by an ATPase helicase loader. However, most bacteria do not encode homologs to the helicase loaders in E. coli and B. subtilis, raising the question of how helicase activity is facilitated in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…The PSP system is a great use case to characterize using molecular evolution and phylogeny due to the variety of domain architectures, cellular localizations, and phyletic spreads of each of these protein families and operons. The PSP work, including this Lia operon use case, as well as other recent diverse biological applications [2][3][4][5][6][7][8][9][10][11] indicate that the MolEvolvR approach is invaluable in characterizing new protein families of interest in the context of evolution. Homolog data table with the best hits from all superkingdoms of life (queried across all RefSeq genomes).…”
Section: Phylogeny Finally We Usedmentioning
confidence: 97%
See 2 more Smart Citations
“…The PSP system is a great use case to characterize using molecular evolution and phylogeny due to the variety of domain architectures, cellular localizations, and phyletic spreads of each of these protein families and operons. The PSP work, including this Lia operon use case, as well as other recent diverse biological applications [2][3][4][5][6][7][8][9][10][11] indicate that the MolEvolvR approach is invaluable in characterizing new protein families of interest in the context of evolution. Homolog data table with the best hits from all superkingdoms of life (queried across all RefSeq genomes).…”
Section: Phylogeny Finally We Usedmentioning
confidence: 97%
“…This gap impedes identifying and characterizing the complete molecular systems involved in various critical cellular processes such as molecular pathogenesis, antibiotic resistance, or stress response. Several studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] have demonstrated the power of molecular evolution and phylogenetic analysis in determining molecular functions of such proteins. There are many individual tools [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] for protein sequence similarity searches or ortholog detection, delineating co-occurring domains (domain architectures), and building multiple sequence alignments and phylogenetic trees.…”
mentioning
confidence: 99%
See 1 more Smart Citation